Distance to alveolar crestal bone: a critical factor in the success of orthodontic mini-implants - Ramzi Haddad; Maria Saadeh (SpringerOpen, 2019)
Abstract Background To evaluate the success rate of orthodontic mini-implant (MI) in relation to implant characteristics, mainly implant distance to alveolar crestal bone (AC) and root proximity (RP) to adjacent teeth. Methods Two hundred sixty MIs (209 in maxilla, 51 in mandible) were categorized into success (n = 229) and failure (n = 31) groups. Distances from MI to the most adjacent tooth (DT) and to AC level (DC) were measured on periapical radiographs taken with the orthoradial projection technique. Appropriate statistical tests (chi-square, t test, logistic regression) were applied. Results DC measurements were statistically significantly greater in the success group (7.46 ± 1.7 mm) compared to 3.43 ± 0.81 mm in the failure group. Root proximity was not associated with miniscrew failure. Patient age, mini-implant site, and DC were significant predictors of mini-implant failure (p < 0.001), which decreased significantly with increasing age (Coef = − 0.345; p = 0.013) and when the mini-implant was placed between premolars (p = 0.028) or between premolar and first molar (p = 0.045). The probability of failure also decreased with increasing DC distance (Coef = − 3.595; p < 0.001). Conclusion The distance to alveolar crest was strongly associated with long-term stability. More apical placement of the MI from the crest would be compatible with a denser and thicker bucco-lingual/palatal bone level.